Informality in Medellín through the Lens of Governance - Calderon, Edwar; Eslava, Adolfo; Mejia-Dugand, Santiago (Universidad del Rosario, 2020)
Cities in the global South have received attention in global governance and sustainability discussions. This seems to be a logical result, considering that most people in the world live inthem. In particular, Medellín has received important attention thanks to a series of urban interventionsrelated to the improvement of different aspects of the quality of life of its inhabitants. In this article we discuss how governance is materialized and takes different shapes depending on the conditions and actors in each specific case. Additionally, we explore the case of Juan Bobo, a housing consolidation pilot project that took place in the city of Medellín. Through this case, we try to understand how governance takes shape under informal conditions andhow can different functional combinations of governance styles be achieved to solve some of the problems that affect self-built neighborhoods in the city.